Comparison of Post Biopsy Pathology and Post Radical Prostatectomy Pathology in Patients with Prostate Cancer Detected After Fusion Biopsy - Serdar Göktaş; Murat Celik; Halil Özer; Murat Gül; Ali Furkan Batur; Özcan Kılıç; Mehmet Kaynar; Emre Altıntaş (Genel Tıp Dergisi)
Aims: To compare the post-radical prostatectomy (RP) final pathologies and post-biopsy pathologies of the patients diagnosed with prostate cancer (PCa) after fusion biopsy according to the International Society of Urological Pathology (ISUP) grading system. Material and Methods: In this retrospective study, data of 182 patients who underwent fusion biopsy and concomitant systematic biopsy between January 2020 and August 2022 was reviewed. All these patients were biopsy naive with PIRADS-3 lesions according to the multiparametric MRI (mp-MRI) imaging. A total of 89 patients with PCa detected by biopsy were included in the study. Age, PSA, PSA density, and lesion grades according to PI-RADS were analysed. The post-biopsy (fusion and systematic biopsy) pathology results of 60 patients who underwent RP were compared with the final pathology results after RP. Results: Pathological results after fusion biopsy and RP were compared. The individual agreement between RP and fusion biopsy for each ISUP grade was moderate to almost excellent (0.558 to 0.848). When the overall agreement between RP and fusion biopsy was evaluated, the weighted kappa was calculated as 0.721 (95% CI: 0.577 to 0.865), which was determined as substantial significant agreement. On the other hand, the overall agreement between systematic biopsy and pathology results after RP was calculated as weighted kappa 0.544 (95% CI: 0.405 to 0.683) and this agreement was determined as moderate agreement. Conclusion: Our study showed that the concordance between the pathology result after fusion biopsy and the final pathology after RP was higher than the standard TRUS prostate biopsy. We think this compliance is crucial in the regulation and follow-up of the treatment of the patients.